Verbalization of evaluation in prose and dramatic genres - Sukalenko, Tetiana (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article deals with the study of the peculiarities of linguistic expression of the category of assessment, which as a universal language category operating at different language levels, plays an important role in the choice of native speakers and, consequently, culture, language means of information and is equally important for mental processes of perception, comprehension and acceptance or non-acceptance of this information. The publications in the scientific literature on various aspects of the study of the category of evaluation in terms of language have been reviewed. The analysis of the peculiarities of verbalization of the category of evaluation is carried out on the material of fictional and dramatic discourse, which is a productive language environment for studying the category of evaluation, because through verbalized national-cultural ideas and stereotypes are reflected the conceptual and linguistic pictures of the world. First of all, this category is manifested in the language and characteristics of the characters. Special attention is paid to the characters of a (chynovnyk, pan, a pani, a panna and a cossack, verbalized in the fictional and dramatic discourse of the XIX century. Evaluative characteristics, which are the elements of language modeling of fictional images, served as a basis for distinguishing the following types of evaluation: positive and negative evaluation in the structure of the text narrative, neutral evaluation, hidden positive evaluation, author’s evaluation, evaluation by other characters. A positive evaluation in the language of fiction is shown by the linguistic means of creating the character of a cossack. Negative assessment was found in the linguistic means of creating the image of the pan (landlord), the images of the pani and panna are ambivalent. Evaluation is present both in the language of the characters and in the author’s characteristics or comments. The object of evaluation in the fictional and dramatic genres can be both internal and external characteristics of the characters, and external characteristics are often marked by positive evaluation, while internal features have either negative or ambivalent evaluation characteristics. It was found that the ways of realization of positive or negative evaluation in the language of fiction are quite diverse. They depend on the literary and fictional methods, the creative manner of the writer and reflect his worldview.